ISSUES OF LANGUAGE EDUCATION IN RUSSIAN TECHNICAL UNIVERSITIES AND SOLUTIONS FOR THEIR ELIMINATION - Tatiana V. Sidorenko; Svetlana V. Ryboushkina (Высшее образование в России)
Integration of the Russian system of higher engineering education into the global educational domain compelled Russian universities to enhance the importance of humanities in engineering programs with a special focus on learning foreign languages. In the modern interpretation of its functions, a foreign language is considered not only an instrument of cross!cultural communication, but also an essential tool for international professional development and career growth of specialists. However, it must be admitted that the system of language education at a university level comes up against serious problems of historical, economic or political background, for which reason there are processes in the system that hinder or hamper solution of the tasks set before the university. The article makes an attempt to identify the existent problem areas of language education in Russian technical universities, while developing recommendations that can contribute to improvement of the current situation.